Factors Affecting Disclosure in South African HIV-Positive Pregnant Women - Makin, Jennifer D (Mary Ann Liebert, Inc., 2008)
To provide understanding of social and psychological factors that affect disclosure of HIV status among women diagnosed HIV-positive in pregnancy, 438 HIV positive women attending antenatal clinics in Pretoria, South Africa were invited to participate in a longitudinal study. A total of 293 (62%) women were enrolled from June 2003 to December 2004. Questionnaires assessing sociodemographics and psychological measures were administered during pregnancy and at 3 months postdelivery. At enrollment, 59% had disclosed to their partners and 42% to others. This rose to 67% and 59%, respectively, by follow-up. Logistic regression analysis identified being married (adjusted odds Ratio [AOR] 2.32; 95% confidence interval [CI] 1.20–4.47), prior discussion about testing (AOR 4.19; CI 2.34–7.49), having a partner with tertiary education (AOR 2.76; CI 1.29–5.88) and less experience of violence (AOR 0.48; CI 0.24–0.97) as factors associated with having disclosed to partners prior to enrollment. Better housing (AOR 1.26; CI 1.06–1.49), less financial dependence on partners (AOR 0.46; CI 0.25–0.85), and knowing someone with HIV (AOR 2.13; CI 1.20–3.76) were associated with prior disclosure to others. Increased levels of stigma at baseline decreased the likelihood of disclosure to partners postenrollment (AOR 0.91; CI 0.84–0.98) and increased levels of avoidant coping decreased subsequent disclosure to others (AOR 0.84; CI 0.72–0.97). These results provide understanding of disclosure for women diagnosed as HIV positive in pregnancy, and identify variables that could be used to screen for women who require help.